EFEKTIFITAS PELAYAN PUBLIK PASCA PEMEKARAN KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR TAHUN 2010 – 2014 - Febie Valdo Nantes; wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
One of the many reasons in Koto Kampar Hulu district’s unfoldment is the increasing of people’s request for quality service. The challenge in giving the quality service is not only to give efficient service, but also to give the service evenly to all people without looking at their social status. In other word, the challenge is to give a fair and democratic serviceThe purpose of this research are (1) to find out the effective of public service after the unfoldment of koto kampar hulu district, kampar regency. (2) to find out factors that influence the effectivity of public service in Koto kampar huku district, Kampar regency.This is a qualitative research. This research was done in Koto kampar hulu district, kampar regency. Data collecting technique in this research are (1) observation and (2) interview.The results showed that the effective of public service of koto kampar hulu district, kampar regency be applicable dimensions Tangibel, Realiability, Responsiviness, Assurance dan Emphaty. But has not run in accordance with wishes of the people, which is an inconvenience places including facilities and infrastructure services are not yet complete, yet masterfully employees in using the tools of the service, and the unkindness of employees in the service process.Key words: the effectivity, public service.